Simulation of the clinical procedure by digital intraoral palpation of the greatest prominence of the Infrazygomatic crest for mini-implants insertion (Research, Society and Development, 2022)
The objective of this cross-sectional retrospective study was to simulate using cone-beam computed tomography (CBCT) in adults, the clinical procedure performed by intraoral digital palpation of the greatest prominence (GP) of the Infrazygomatic crest (IZC) for mini-implants (MIs) insertion. CBCT images of 34 adults (14 men, 20 women), aged 18.0 to 57.7 years (mean, 32.2 years) were selected. On 3D reconstruction, the GP of the IZC region was determined using the anatomical morphology, and its anteroposterior position on the selected axial slice was evaluated relative to the dental reference located between the maxillary first and second molars (U6–U7). On the selected coronal slice, two reference lines were established to evaluate the insertion angle and insertion depth (IZC thickness) for MIs. The same procedure was performed on slices with intervals of 1 mm mesially as well as distally up to reach 4 mm. The right and left sides were measured. In relation to U6-U7, the GP of the IZC was 0.19 mm (±1.79) mesial on the right side and 0.29 mm (±1.65) mesial on the left side. The greatest bone thickness of the IZC was 4.95 mm (±2.39) on the right side, 3.81 mm distal from U6-U7, and 4.79 mm (±2.13) on the left side, 3.71 mm distal from U6-U7. The GP-IZC determined visually on the 3D reconstruction, did not present the greatest bone thickness. The bone tended to gradually become thicker distal to the GP-IZC and the dental reference U6-U7.